Improving Medication Administration Safety: Using Naïve Observation to Assess Practice and Guide Improvements in Process and Outcomes. Issue 6 (November 2014) - Donaldson, Nancy; Aydin, Carolyn; Fridman, Moshe; Foley, Mary
Abstract Purpose To present findings from the Collaborative Alliance for Nursing Outcomes' (CALNOC) hospital medication administration (MA) accuracy assessment in a sample of acute care hospitals. Aims were as follows: (1) to describe the CALNOC MA accuracy assessment, (2) to examine nurse adherence to six safe practices during MA, (3) to examine the prevalence of MA errors in adult acute care, and (4) to explore associations between safe practices and MA accuracy. Methods Using a cross‐sectional design, point in time, and convenience sample, direct observation data were collected by 43 hospitals participating in CALNOC's benchmarking registry. Data included 33, 425 doses from 333 observation studies on 157 adult acute care units. Results reveal that the most common MA safe practice deviations were distraction/interruption (22.89%), not explaining medication to patients (13.90%), and not checking two forms of ID (12.47%). The most common MA errors were drug not available (0.76%) and wrong dose (0.45%). The overall percentage of safe practice deviations per encounter was 11.40%, whereas the overall percentage of MA errors was 0.32%. Conclusions and Implications Findings predict that for 10, 000 MA encounters, 27, 630 safe practice deviations and 770 MA errors will occur. A 36% reduction in practice deviation per encounter prevents 4.4% MA errors. Ultimately, reliably performing safe practices improves MA accuracy.